Pragmatics In The Translation Of Taqdim Verses In The Quran Juz 30 - Nurmala, Mia; Al-Farisi, Muhammad Zaka (Dzil Majaz: Journal of Arabic Literature, 2023)
Pragmatic sentences are contained in verses of the Qur'an that have a distinctive style of language and nuance of sentences. Taqdim or precedence becomes its own beauty in the order of the word style of Al-Quran. In addition to the beauty of the style of language has a goal or meaning that will affect its readers. However, this may not be achieved well in a translation because of the lack of understanding. Therefore this study aims to present the pragmatic translation of taqdim on muta'aliqat jar from amilnya in Al-Quran Juz 30. The research method used is literature study method with purposive research design. The results of this research on Juz 30 indicate the beauty of the style of Al-Quran language that has its own meaning and purpose. The purpose of taqdim on muta'aliqat jar from its amil among others istikhshash, ta'lilul adzab akbar, tasydidul wa'id.